Evaluasi Program Corporate Social Responsibility Beasiswa WTON Membangun Masa Depan dengan Perhitungan Social Return on Investment - Hawari, Alhilal Yusril (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
PT Wika Beton Tbk., as one of Indonesia’s State-Owned Enterprises, is committed to contributing to social development through its Corporate Social Responsibility programs. One of these initiatives is realized through the “WTON Building the Future” Scholarship Program. Policy evaluation is essential in community development programs to identify, assess, and measure the social impact generated by the program. The evaluation was conducted using the Social Return on Investment (SROI) analysis. This research uses a mixed methods approach with a sequential explanatory design. Quantitative data is collected to provide a general overview, followed by qualitative data to deepen understanding of the initial findings. Quantitative data was obtained through the distribution of questionnaires. Qualitative data was collected through in-depth interviews. Based on the research results, it is concluded that the WTON Building the Future Program has been running with clear conceptualization and design, has program implementation, accountability through proper reporting, and visible usefulness of the program related to impact and efficiency. This is based on the analysis result, which shows that the program has an outcome value greater than the value of the investment provided. Based on the indicators and dimensions mentioned, it can be conclude that the implementation of the WTON Building the Future Scholarship Program Policy Evaluation has been successful by fulfilling all the indicators in the policy evaluation theory according to Rossi dan Freeman and having an outcome value greater than the investment value based on the results of the Social Return on Investment (SROI) calculation.